Repossessing Border Space: Security Practice in North American Border Art. (1st October 2016) - Heide, Markus
Abstract: This paper discusses how the visual arts engage in representing border crossing experiences and, more specifically, how art interrupts border security practices and their rituals. After introducing the history of North American border art and different approaches to issues of border crossing, the paper will concentrate on specific works. It argues that the selected works of art perform interventions that confront the public with the borderlands as a place of violence and death. At the same time, artists are shown to employ different artistic strategies of symbolically re-possessing the borderlands for undocumented migrants who – when crossing it – experienced it as an existential obstacle.